2005
DOI: 10.1080/01431160500227847
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of coastal phytoplankton features by optical remote sensors: comparison with a regional ecosystem model

Abstract: Different scales of hydrological and biological patterns of the Bay of Biscay are assessed using space-borne and airborne optical remote sensing data, field measurements and a 3-dimensional biophysical model. If field measurements provide accurate values on the vertical dimension, ocean colour data offer frequent observations of surface biological patterns at various scales of major importance for the validation of ecosystem modelling. Although the hydrobiological model of the continental margin reproduces the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Because the model mostly focuses on productive fronts with low chl a contents, the results suggest that, at a mesoscale, chl a horizontal gradients prevail over chl a levels regarding the energy flux across the pelagic food web of the Mediterranean Sea. It is worth noting that the sampling grids of field campaigns are often too large to properly describe the dynamics of fronts (see example in Druon et al 2005) or the related variability of small or large zooplankton populations (see the sampling grid for the Ligurian Sea in McGehee et al 2004). This approach replies to the need for explicit statements about the niche theory assumed in species distribution modelling as shown by Austin (2007).…”
Section: Selection Of Methods and Predictorsmentioning
confidence: 99%
“…Because the model mostly focuses on productive fronts with low chl a contents, the results suggest that, at a mesoscale, chl a horizontal gradients prevail over chl a levels regarding the energy flux across the pelagic food web of the Mediterranean Sea. It is worth noting that the sampling grids of field campaigns are often too large to properly describe the dynamics of fronts (see example in Druon et al 2005) or the related variability of small or large zooplankton populations (see the sampling grid for the Ligurian Sea in McGehee et al 2004). This approach replies to the need for explicit statements about the niche theory assumed in species distribution modelling as shown by Austin (2007).…”
Section: Selection Of Methods and Predictorsmentioning
confidence: 99%
“…Satellite-derived maps are now routinely provided to a large community of users through a web site (http://cersat.ifremer.fr/data/view/nausicaa/nausicaa_tutorial). Providing validation and calibration data to regional biogeochemical models is a major application of satellite remote sensing in these waters (Druon et al, 2005;Ménesguen and Gohin, 2006;Ménesguen et al, 2007;Lacroix et al, 2007). Mineral SPM derived from satellite data are also used to force the light availability at the end of winter in a biological model of the Bay of Biscay (Huret et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding body shape, the Spanish individuals, although bigger in SL (Table 1), after size allometric correction were found to have the smallest body measurements (75% of the total recorded distances), namely in terms of head length, heights and widths, the majority of fin lengths and distances and the anterior and posterior fish heights (DT1, DT3-DT13, DT15-DT19, DT25 and DT28 and DT37). The hydrology of the Spanish sampling location (Bay of Biscay) is particularly complex due to interactions between the general oceanic circulation, topography, highly energetic tidal currents, wind-induced currents and river inputs of freshwater, mainly located on the French coast [55,56]. Other authors have reported that body, head and fins in fish are highly affected by water velocity and fish with a streamlined morphology exhibit enhanced capability to counter hydrodynamic resistance within fast-flowing water [57][58][59].…”
Section: Discussionmentioning
confidence: 99%